Who is prepared for the new digital age? Evidence from the EIB Investment Survey - European Investment Bank (European Investment Bank, 2020)
In the fight against the Coronavirus, digital technology is playing an unprecedented role in the maintenance of daily life and economic and social activities, as well as the recovery of industries and business activities. The Coronovirus-pandemic could become a tipping point for digitalisation - a dawn of a new era - by accelerating the maturity of digital technology: What was once a 'nice to have' could now become a 'crucial to have'. This report analyses investment in and adoption of digital technologies by firms in the EU and the USA and provides evidence on better performance of digital firms compared to non-digital ones. The report draws from two unique sets of data, including the European Investment Bank Survey (EIBIS) 2019, and the EIBIS Start-up and Scale-up Survey 2019.